Parasites of urological importance - Kehinde, E.O.; Anim, J.T.; Hira, P.R. (Urologia Internationalis, 2008)
With the world increasingly becoming a global village, transnational and transcontinental migration has become the order of the day. It is expected that migrants will take with them some diseases (including parasites) which are normally endemic in their countries of origin, to their host countries. Similarly, environmental changes that result from development of water resources, global warming, growth and migration of population can facilitate the spread of parasites. In this review we describe the epidemiology, presentation, diagnosis and treatment options of parasites that urologists may encounter. Notably among these parasites are Schistosoma haematobium, Echinococcus granulosus, Wuchereria bancrofti and Onchocerca volvulus.
Keywords: Diagnosis; Epidemiology; Genitourinary tract; Parasites; Treatment